The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1155/s1073792804132133
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: http://imrn.oxfordjournals.org/ Downloaded from 186 Sun-Yung A. Chang et al. Theorem 1.1.Let Ω ⊂ S n (n ≥ 5) be an open connected subset and let g S n be the standard metric on S n . Assume that there exists a metric g on Ω such that (Ω, g) is complete, g is conformal to g S n , |R| + |∇ g R| g ≤ c 0 , σ 1 (A) ≥ c 1 > 0, and σ 2 (A) ≥ 0, then dim(S n \Ω) < (n − 4)/2.On the other hand, we have the following theorem.Theorem 1.2. Let Ω ⊂ S n (n ≥ 3) be an open connected subset and let g S n be the standard metric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Geometrically, for any positive solution u of the equation (1.1), the corresponding conformal metric g h u 4 n 2 jdxj 2 has a constant scalar curvature R g h n.n 1/.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Geometrically, for any positive solution u of the equation (1.1), the corresponding conformal metric g h u 4 n 2 jdxj 2 has a constant scalar curvature R g h n.n 1/.…”
Section: Introductionmentioning
confidence: 99%
“…We always assume that u has a nonremovable singularity at x h 0. Refer to [9] and its references for more information concerning the k -Yamabe equation, and in particular to [4], [6], and [7] for the size of the singular sets, and to [14] and [15] for the existence of solutions with isolated singularity.…”
Section: Introductionmentioning
confidence: 99%
“…Another testing ground is to consider closed locally conformally flat manifolds. Then the recent works in [Chang et al 2004] and [González 2005] indicate to us that the positivity of fourth-order curvature is indeed very informative about the topology of the underlying manifolds. We would also like to mention the work by Xu and Yang in [2001] where they demonstrated that positivity of the Paneitz-Branson operator is stable under the process of taking connected sums of two closed Riemannian manifolds.…”
Section: Introductionmentioning
confidence: 95%
“…The positivity of Paneitz invariant in dimension higher than 4 should be a topological constraint, as indicated by successful researches in [Chang and Yang 2002] (references therein) for a fourth-order analogue of how Gaussian curvature influences the geometry of surfaces in dimension 2. Another testing ground is to consider closed locally conformally flat manifolds.…”
Section: Introductionmentioning
confidence: 99%